2021
DOI: 10.1007/s10815-021-02119-y
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of men infected with COVID-19 for presence of SARS-CoV-2 virus in their semen

Abstract: Introduction Whether severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can be detected in semen and transmitted sexually is a vital question that has, thus far, been inconclusive. Prior studies, with limited numbers, have included men in various stages of infection with most in the recovery phase of the illness. The timing of test results and severity of illness has made recruiting study participants a significant challenge. Our pilot study will examine semen from men with a recent dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 6 publications
2
19
1
7
Order By: Relevance
“…This study reported no evidence of SARS-CoV-2 in the semen, seminal plasma, and spermatozoa pellet samples of 31/32 (97%) enrolled COVID-19 patients in the acute phase of the disease, in line with previous studies [22][23][24]. However, we detected the presence of SARS-CoV-2 within the semen sample and the seminal plasma fraction of one COVID-19 patient (3%) in the acute stage of the disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study reported no evidence of SARS-CoV-2 in the semen, seminal plasma, and spermatozoa pellet samples of 31/32 (97%) enrolled COVID-19 patients in the acute phase of the disease, in line with previous studies [22][23][24]. However, we detected the presence of SARS-CoV-2 within the semen sample and the seminal plasma fraction of one COVID-19 patient (3%) in the acute stage of the disease.…”
Section: Discussionsupporting
confidence: 90%
“…In a first study from China, Pan et al investigated single semen samples from 34 recovering COVID-19 patients but did not find any trace of SARS-CoV-2 [15]. These results were confirmed by other cohort studies cumulating 342 COVID-19 patients [16][17][18][19][20][21][22][23]. It should be noted that 63 and 279 of these patients were in the acute (< 8 days from the onset of the symptoms or diagnosis) and recovery phases of the disease, respectively.…”
Section: Introductionmentioning
confidence: 91%
“…18 Conversely, an American study of 18 men with mild or moderate COVID-19 symptoms (none requiring hospitalisation) produced no positive results. 19 The direct effect of the virus on semen is unknown. In a longitudinal cohort study of 84 men with COVID-19 infection requiring hospitalisation, all standard WHO criteria for semen analysis were significantly impaired.…”
Section: Male Factor Infertilitymentioning
confidence: 99%
“…Figura 1. Diagrama de flujo que muestra el proceso de selección de artículos Al momento de la revisión, existían once estudios (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) : ocho de cohorte, uno observacional, un reporte de caso y un estudio piloto (Tabla 1), que reportan la evaluación del semen de hombres infectados con SARS-CoV-2. En total, 296 muestras fueron recolectadas en conjunto, tomadas desde el día 1 hasta 112 días después de que el paciente mostró un resultado positivo a una prueba RT-PCR nasofaríngea para SARS-CoV-2 (Figura 2), y todas, excepto ocho, fueron negativas para la presencia del virus (2) .…”
Section: Resultsunclassified
“…Recientemente, Burke et al (2021) (25) informaron los resultados negativos del análisis de semen de 18 pacientes que se sometieron a extracción de ARN viral y procesados mediante RT-PCR para detectar el SARS-CoV-2. Concluyeron que el virus se encuentra ausente en el semen durante la fase aguda o la convalecencia de la COVID-19.…”
Section: Autorunclassified